Does infection of 2019 novel coronavirus cause acute and/or chronic sialadenitis?. (July 2020) - Wang, Chenxing; Wu, Heming; Ding, Xu; Ji, Huan; Jiao, Pengfei; Song, Haiyang; Li, Sheng; Du, Hongming
Abstract: 2019 novel coronavirus (2019-nCoV) is widespread in China and other countries. The target of 2019-nCoV and severe acute respiratory syndrome coronavirus (SARS-CoV) is angiotensin-converting enzyme 2 (ACE2) positive cells. ACE2 is present in the salivary gland duct epithelium, and thus it could be the target of 2019-nCoV and SARS-CoV. SARS-CoV-related animal model experiments show that it can infect the epithelial cells on the salivary gland duct in Chinese rhesus macaques by targeting ACE2. Clinical studies confirmed that 2019-nCoV and SARS-CoV could be detected in saliva of human patients. We hypothesize that the infection of 2019-nCoV and SARS-CoV will lead to inflammatory pathological lesions in patients' target organs, and possibly inflammatory lesions in salivary glands. 2019-nCoV may cause acute sialoadenitis in the acute phase of infection. After the acute phase, chronic sialoadenitis may be caused by fibrosis repairment. Although there was no direct evidence to prove this, the available indirect evidence indicates a high probability of our hypothesis.